Linguistic analysis of pro-ISIS users on Twitter. (2nd July 2020) - Torregrosa, Javier; Thorburn, Joshua; Lara-Cabrera, Raúl; Camacho, David; Trujillo, Humberto M.
ABSTRACT: The present study analyzed the differences in the language usage between pro-ISIS users and random users on Twitter. Based on the literature, it was expected that, when comparing the tweets from both samples, distinctive patterns would be found on their usage of similar linguistic categories. This observational study compared a dataset of 105 pro-ISIS users with 91 random Twitter users, both collected between 2015 and 2016. The Linguistic Inquiry Word Count (LIWC) software was employed to analyze the terminology used by both groups from a quantitative perspective. Relevant LIWC categories used in previous studies were included in the assessment. ISIS supporters used significantly more third person plural pronouns and less first person singular and second person pronouns. They also used more words related with death, certainty, and anger than the random group, along with more words containing six letters or more. Finally, more negative language and tone was used by the pro-ISIS group. The language used by ISIS supporters on Twitter was discussed, as well as comparisons to relevant studies on other political extremists. Ultimately, our results suggest that broad similarities in language usage exist between ISIS supporters and other extreme ideologies.